2021
DOI: 10.3390/pharmaceutics13010059
|View full text |Cite
|
Sign up to set email alerts
|

Aerosolized Niosome Formulation Containing Gemcitabine and Cisplatin for Lung Cancer Treatment: Optimization, Characterization and In Vitro Evaluation

Abstract: Gemcitabine (Gem) and cisplatin (Cis) are currently being used for lung cancer treatment, but they are highly toxic in high dosages. This research aimed to develop a niosome formulation containing a low-dosage Gem and Cis (NGC), as an alternative formulation for lung cancer treatment. NGC was prepared using a very simple heating method and was further optimized by D-optimal mixture design. The optimum NGC formulation with particle size, polydispersity index (PDI), and zeta potential of 166.45 nm, 0.16, and −15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 49 publications
2
14
0
Order By: Relevance
“…Furthermore, synergistic effects of CIS in combination with anticancer drugs such as gemcitabine and paclitaxel have been investigated against breast cancer and other diseases. 15 , 60 , 61 Remarkably, as in our research, FPNCE yielded CIs lower than 1, which indicated synergism.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, synergistic effects of CIS in combination with anticancer drugs such as gemcitabine and paclitaxel have been investigated against breast cancer and other diseases. 15 , 60 , 61 Remarkably, as in our research, FPNCE yielded CIs lower than 1, which indicated synergism.…”
Section: Discussionsupporting
confidence: 81%
“…It has been reported that the incorporation of fluorine into this small molecule—triazole—imparts a significant enhancement to their biological activities in comparison to their non-fluorinated counterparts ( Langer et al, 2011 ; Ali et al, 2013 ), for instance, fluconazole and gemcitabine. Until now, modifications of the triazole moiety have proved to be highly effective with lesser toxicity and improved potency ( Mohamad Saimi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that the optimized formulation had reduced cytotoxicity against both MRC5 and A549 cell lines when compared with the control system (Gem + Cis alone) from highly toxic (IC50 < 1.56 µg/mL) to weakly toxic (IC50 280.00 µg/mL) and fairly toxic (IC50 = 46.00 µg/mL), respectively, after 72 h of treatment. These findings promised that the optimized aerosolized niosomal formulation has excellent anti-tumor activity and can be used as promising drug delivery system 7 .…”
Section: Aerosolized Niosomes With Anti-cancer Potentialmentioning
confidence: 90%